Selected Papers from the 1st International Online Conference on Nanomaterials - Díez-Pascual, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book compiles selected papers from the Proceedings of the 1st International Online Conference on Nanomaterials, held 1-15 September, 2018 on sciforum.net, an online platform for hosting scholarly e-conferences and discussion groups. It targets a broad readership of physicists, chemists, materials scientists, biologists, environmentalists, and nanotechnologists, and provides interesting examples of the most recent advances in the synthesis, characterization, and applications of nanomaterials.